Experimental study on the efficacy of a hybrid artificial nerve: The hot dog method. Issue 10 (October 2021) - Tamura, Ryosuke; Hashikawa, Kazunobu; Sakakibara, Shunsuke; Osaki, Takeo; Kitano, Daiki; Maruguchi, Hayato; Nomura, Tadashi; Sugiyama, Daisuke; Terashi, Hiroto
Introduction: We hypothesized that hybrid artificial nerves might overcome the limitations of a nerve conduit by isolating nerve fascicles from autologous nerves. Nerve sacrifice during harvest, a drawback of conventional autologous nerve transplantation, may be reduced by the hot dog method. The hot dog method (based on the morphology of hybrid artificial nerves) adds nerve conduits to autologous nerve fascicles. Methods: Forty-eight rats with a 10-mm sciatic nerve defect were divided into six groups ( n  = 8 per group) according to the neural reconstruction method: autologous nerve transplantation, the hot dog method, nerve conduit, nerve fascicle transplantation, sham control, and nerve fascicle isolation were classified as Groups I, II, III, IV, V, and VI, respectively. The sciatic nerve function was assessed in these groups, a histological evaluation was performed, and statistical analyses were conducted based on these data. Results: Group III (nerve conduit) and Group IV (nerve fascicle transplantation) showed the lowest functional and axonal regenerative effects, followed by Group II (hot dog method) and Group I (autologous nerve transplantation). Group VI (nerve fascicle isolation) tended to achieve better recovery in motor function and axonal regeneration than Group I (autologous nerve transplantation). Conclusions: The hot dog method is simple, safe, and easy to execute. This method can serve as a new neural reconstruction method that uses artificial nerves.